Extensive Geotechnical Instrumentation Program to Control Dike Raising Constructed on Soft Clay - Mahmoud Tabbal; Ziad Mansour (Semesta Teknika, 2009)
In its quest of increasing potash production, Arab Potash Company (APC) decided to increase the size of their salt evaporation pans. The Dike 18 which is spanning a length of 13km and enclosing a pan area of 16.5km2 was built between January 1996 and December 1997 as part of APC's expansion scheme. The foundation soils were predominantly varies from soft to very soft silty clay. From laboratory and field test results the undrained shear strength of the clay was between 28 to 40 kPa. An extensive instrumentation program was designed and implemented in order to control the dike raising during construction as well as to monitor the performance of the dike foundation during and after the construction. Instrumentations being installed included settlement spider magnets, level stations, standpipe and pneumatic piezometers. The major constraints of the instrumentation program were the large vertical settlements (2-3m) of the very soft clays, artesian conditions where sand and salt layers were present, high salinity of the groundwater and the development of sinkholes. Special installation and protection measures were developed to overcome these constraints. The performance aspects of the instruments were discussed and typical plots were presented.